2018
DOI: 10.1080/08998280.2017.1416237
|View full text |Cite
|
Sign up to set email alerts
|

Use of neuromuscular blocking agents in acute respiratory distress syndrome

Abstract: Acute respiratory distress syndrome is the result of an acute inflammatory response of the lungs, causing severe hypoxemia. A variety of therapeutic modalities have been extensively studied, with only a few demonstrating improvement in survival. Specifically, mechanical ventilation with use of low tidal volumes, prone positioning, and treatment with neuromuscular blocking agents have proven beneficial. This article focuses on the utilization of neuromuscular blocking agents in this entity. In particular, we br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 30 publications
(29 reference statements)
0
6
0
Order By: Relevance
“…Observing one to two twitches correlates with 80 to 90% blockade of neuromuscular junctions. 76 We believe if PNS monitoring is used a goal of one to two twitches, in conjunction with a clinical assessment, is a reasonable starting point. A clinical assessment is recommended by SCCM due to variability in muscular response to temperature, peripheral edema, variations in devices, and variability in staff training and experience.…”
Section: Dosing Monitoring and Durationmentioning
confidence: 99%
“…Observing one to two twitches correlates with 80 to 90% blockade of neuromuscular junctions. 76 We believe if PNS monitoring is used a goal of one to two twitches, in conjunction with a clinical assessment, is a reasonable starting point. A clinical assessment is recommended by SCCM due to variability in muscular response to temperature, peripheral edema, variations in devices, and variability in staff training and experience.…”
Section: Dosing Monitoring and Durationmentioning
confidence: 99%
“…Considering the bolus and continuous infusion protocols, our group recently published a paper comparing the protocols in mice during normal aging process. 32 We found that the bolus and continuous infusion protocols could differentiate the CPM parameters among different ages with four (30, 100, 300, and 1000 mgÁkg À1 for bolus) and three (48,96, 192 mgÁkg À1 Ámin À1 for continuous infusion) doses of MCh (Table 2). Additionally, the main parameter affected by the aging process was the elastance, and the observed differences were similar in the two protocols.…”
Section: Mch Infusionmentioning
confidence: 92%
“…Neuromuscular blockers (NMBAs) act on nicotinic cholinergic receptors at the neuromuscular junction to impair the transmission of nerve impulses, which result in muscle relaxation. 48 Currently, there are several drugs that belong to the NMBAs class; however, pancuronium, vecuronium, and rocuronium do not seem to interfere with lung function. 49 Routes of administration are generally intravenous and intraperitoneal; doses vary widely.…”
Section: Muscle Blockersmentioning
confidence: 99%
“…Atracurium is a benzylisoquinolinium non‐depolarizing neuromuscular blocking agent that can be used to improve patient synchrony during mechanical ventilation (MV) 1‐4 . Atracurium is metabolized by both Hofmann elimination, degrading spontaneously at body temperature and pH, and ester hydrolysis by plasma esterases 1‐4 . As metabolism is independent of hepatic and renal function, it is a useful neuromuscular blocking agent in critically ill patients that may have varying degrees of organ dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…Degradation of atracurium produces laudanosine, which undergoes hepatic metabolism and predominantly renal excretion 1,2 . Laudanosine has been associated with central nervous system excitement and seizures in people 1‐2,4 and its administration has been documented to cause seizures under experimental conditions in dogs at doses of 14‐22 mg/kg 3 . No data are available in animal models that determine the corresponding atracurium dose required to reach these concentrations.…”
Section: Introductionmentioning
confidence: 99%